2001
DOI: 10.1097/00005768-200103000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of nandrolone decanoate in fast and slow rat skeletal muscles

Abstract: These results show that 5 wk of exercise training produced changes in the contractile responses developed by isolated skeletal muscle cells. The combination of exercise training with ND treatment potentiated these effects, suggesting that there was some modification in the excitation-contraction coupling mechanism. ND treatment also produced a more potent effect in soleus than edl sedentary muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
24
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 28 publications
11
24
0
4
Order By: Relevance
“…This section of our finding is accordance with those of Lindqvist and Fahlke which reported that ND-treated rats water consumption was significantly higher than those of control group [20]. Higher food and water intake in test groups may be due to ND cause alter metabolism in skeletal muscle and alteration in the excitation-contraction coupling mechanism [21]. Lindblom et al reported that ND treatment affected on proopiomelanocorthin (POMC) production and affected food intake in rats [22].…”
Section: Discussionsupporting
confidence: 91%
“…This section of our finding is accordance with those of Lindqvist and Fahlke which reported that ND-treated rats water consumption was significantly higher than those of control group [20]. Higher food and water intake in test groups may be due to ND cause alter metabolism in skeletal muscle and alteration in the excitation-contraction coupling mechanism [21]. Lindblom et al reported that ND treatment affected on proopiomelanocorthin (POMC) production and affected food intake in rats [22].…”
Section: Discussionsupporting
confidence: 91%
“…This chamber, with an open-topped channel 1.3 ϫ 1.3 ϫ 25.0 mm, has at one end a four-way tap that opens directly into the channel, allowing rapid change of the perfusion solution (Ͻ0.2 s), or into a drain so that perfusion by stagnant solutions is avoided. The preparation was mounted as described by Joumaa and Léoty (2001). Briefly, one tendon of the preparation was snared under a fine silver loop and fixed in the open-topped channel.…”
Section: Methodsmentioning
confidence: 99%
“…AAS cause both the increased synthesis and decreased catabolism of muscle proteins [34]. They trigger muscle hypertrophy and protein synthesis, resulting in greater muscle mass and strength, and reduce recovery time by blocking the catabolic effects of cortisol [4,5,[47][48][49]. As a result, AAS are useful in treating chronic wasting conditions such as cancer and AIDS [50,51].…”
Section: Therapeutic Use Of Aasmentioning
confidence: 99%